Intelligent buildings and infrastructure with sustainable and social values - Clements-Croome, Derek (Emerald Publishing Limited, 2024)
Intelligent Buildings and Infrastructure with Sustainable and Social Values, Third edition is a comprehensive guide and an international reference source to the latest knowledge on the design, management, operation and technology of intelligent buildings and cities for sustainable developments that meet the needs of users now and in the future. A transdisciplinary approach underpins the beliefs expressed in the book. Written by authors from industry and academia, the book considers cultural changes affecting the way people live and work, the importance of an integrated approach to design and management, and the benefits technological developments can bring in developing sustainable buildings that meet users' needs and those to mitigate climate change.